THEORETICAL ANALYSIS OF DEFINITION OF CATEGORIES OF COMPETENCE AND COMPETENCE (Pedagogy of Higher and Secondary Education, 2022)
Scientific approaches to competence approach and competence, competency determination are analyzed in the article. The importance of competence approach introduction into theory and practices are stressed.
Keywords: competence approach; competence; competency